The Quest for a Better Environment: Past Experiences and Future Challenges - Danilo C. Israel (Philippine Institute for Development Studies (PIDS), 2002)
The persistence of serious natural resource depletion and environmental degradation means that much remains to be done years into the implementation of Philippine Agenda 21 (PA 21). With this background, the paper reviewed the past experiences and discussed the future challenges faced in the natural resource and environment sector, concentrating on the most important issues still to be addressed in light of PA 21, including those that have policy implications. The purpose was to highlight the issues and promote a more focused discussion. The paper reviewed the natural resource and environmental problems across ecosystems, per ecosystem and per critical resource. Then, it presented a history of natural resources and environmental laws and policies, with PA 21 highlighted, and discussed some of the important gaps and issues. In conclusion, the paper argued that while the implementation of PA 21 may be behind schedule, a determined effort to address the most pressing issues will hasten the attainment of a more sustainable form of development for the country.
Keywords: 330; Philippine Agenda 21; ecosystems approach; natural resource and environmental laws and policies; Umwelt; Umweltpolitik; Umweltrecht; Rohstoffpolitik; Rohstoffvorkommen; Umweltökonomik; Nachhaltige Entwicklung; Philippinen